Surface protective film, optical member, and electronic device
Patent Information
- Application Number
- CN202610445698.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-03-02
- Filing Date
- 2026-04-07
- Publication Date
- 2026-10-23
AI Technical Summary
对于表面凹凸大的偏光板,若贴合以往的追随表面处理的表面保护膜,则存在表面保护膜的粘合剂层不能填满偏光板的表面凹凸,导致气泡滞留,若局部地施加压力,则气泡被挤出,从而与其它部分相比发生变色的问题
[0015]根据本发明,能够提供表面保护膜的粘合剂层充分地追随表面凹凸大的偏光板并表现出高的轻剥离性的表面保护膜、光学部件及电子装置。
Smart Images

Figure CN122956829A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to surface protective films, optical components, and electronic devices for polarizing plates with a surface roughness Ra of 200 nm or higher. Background Technology
[0002] In the electronics field, optical films such as polarizing plates, phase retardation plates, lens films for displays, anti-reflective films, hard coatings, and transparent conductive films for touch panels, as well as optical products such as displays using these films, are in use. When manufacturing and shipping optical products, a surface protective film is applied to the surface of the optical film to prevent surface contamination and damage in subsequent processes (for example, see Patent Document 1).
[0003] When the protective film is transparent, visual inspection of optical products can be performed with the protective film adhered to it. Performing visual inspection with the protective film on eliminates the need to peel off and re-adhere the film, thus improving operational efficiency.
[0004] On the other hand, the number of displays such as digital signage installed in public places is constantly increasing. In cases such as outdoor installations, in order to reduce light reflection, polarizing plates with a surface roughness of more than 200 nm, compared to the previous surface roughness of around 50 nm, are becoming increasingly common.
[0005] Patent Document 1: Japanese Patent No. 6566590 Summary of the Invention For polarizing plates with large surface irregularities, if a surface protective film that follows the conventional surface treatment is applied, the adhesive layer of the protective film cannot completely fill the surface irregularities of the polarizing plate, resulting in trapped air bubbles. If pressure is applied locally, these air bubbles are squeezed out, causing discoloration compared to other areas. Furthermore, while making the adhesive layer of the surface protective film softer or increasing its thickness can help it follow the irregularities, it also increases the peeling force required to remove the protective film, leading to a decrease in yield during the production process.
[0006] Therefore, the present invention was made in view of the above-mentioned problems. The objective is to provide a surface protective film, optical component, and electronic device in which the adhesive layer of the surface protective film can adequately follow a polarizing plate with an uneven surface roughness of 200 nm or more and exhibit high easy peelability.
[0007] The present invention includes the following methods.
[0008] [1] A surface protective film for a polarizing plate with a surface roughness Ra of 200 nm or more, wherein the surface protective film comprises, in sequence, an antistatic layer, a transparent resin film, an adhesive layer, and a separating film, wherein the thickness of the adhesive layer is 12 μm to 25 μm, and the storage modulus G' of the surface protective film after the separating film has been peeled off is 1.8 × 10⁻⁶. 5 When the separator film is applied to the polarizing plate with the surface protective film peeled off, and the peeling force is 1.7 N / 25 mm or less when peeled off from the polarizing plate at a peeling angle of 180° and a peeling speed of 30 m / min, the peeling force is also 1.7 N / 25 mm or less when the separator film is applied with the surface protective film peeled off and a pressure of 2 kgf / cm² is applied. 2 Let A be the proportion of the bubble area before pressurization within the measured field of view, attached to the polarizing plate. A pressure of 5 kgf / cm² will be applied. 2 When the proportion of the bubble area after localized pressurization for 10 seconds within the measured field of view is set as B, the bubble area change rate A-B is less than 3.0%.
[0009] [2] According to the surface protective film described in [1], wherein the polarizing plate is subjected to anti-glare (AG) treatment or anti-glare treatment. Low reflection (AGLR) treatment.
[0010] [3] According to the surface protective film described in [1] or [2], wherein the antistatic layer comprises a conductive polymer and a polyether-modified silicone additive, and the inherent surface resistivity of the antistatic layer is 1.0 × 10⁻⁶. 10 Below Ω / □.
[0011] [4] The surface protective film according to any one of [1] to [3], wherein the adhesive layer is formed by crosslinking an adhesive composition containing an acrylic polymer and a crosslinking agent.
[0012] [5] According to the surface protective film of [4], the adhesive layer further comprises an antistatic agent and / or polyether modified silicone.
[0013] [6] An optical component is formed by attaching the surface protective film of any one of [1] to [5] to the polarizing plate in a state in which the isolation film has been peeled off.
[0014] [7] An electronic device equipped with the optical components described in [6].
[0015] According to the present invention, an adhesive layer capable of providing a surface protective film can adequately follow the surface of a polarizing plate with large surface irregularities and exhibit high easy peelability, as well as surface protective films, optical components, and electronic devices. Attached Figure Description
[0016] Figure 1 This is a cross-sectional view showing an example of a surface protective film with an isolation membrane.
[0017] Figure 2 This is a cross-sectional view showing an example of a surface protective film after the release liner has been peeled off.
[0018] Figure 3 This is a cross-sectional view showing an example of an optical component with a surface protective film attached.
[0019] (Explanation of reference numerals in the attached image) 10, 15… (for polarizing plates) Surface protective film, 11… antistatic layer, 12… transparent resin film, 13… adhesive layer, 14… release film, 20… optical components, 21… adhered material. Detailed Implementation
[0020] The present invention will now be described based on suitable embodiments.
[0021] Figure 1 This is a cross-sectional view showing an example of a surface protective film 10 having an isolation membrane 14. Figure 2 This is a cross-sectional view showing an example of the surface protective film 15 after the release liner 14 has been peeled off. Figure 3 This is a cross-sectional view showing an example of an optical component 20 with a surface protective film 15 attached. The accompanying drawings are conceptual illustrations, and sometimes the dimensions, proportions, etc., of the constituent elements differ from the actual figures.
[0022] The surface protective films (hereinafter also referred to as "surface protective films for polarizing plates") 10 and 15 of this embodiment are surface protective films for polarizing plates that can be used even when the surface roughness of the polarizing plate that becomes the adherend 21 is relatively large. The surface roughness Ra (arithmetic mean roughness) of the polarizing plate is, for example, 200 nm or more. The lower limit of the surface roughness Ra (arithmetic mean roughness) of the polarizing plate is not particularly limited, but is, for example, 250 nm or more, preferably 270 nm or more, and more preferably 280 nm or more. The upper limit of the surface roughness Ra (arithmetic mean roughness) of the polarizing plate is not particularly limited, but is, for example, 500 nm or less, preferably 450 nm or less, and more preferably 420 nm or less. The surface roughness Ra is measured using a non-contact surface roughness measuring instrument according to JIS B 0601 (1994).
[0023] Figure 1 The surface protective film 10 shown comprises, in sequence, an antistatic layer 11, a transparent resin film 12, an adhesive layer 13, and a release film 14. Additionally, Figure 2 The surface protective film 15 shown comprises an antistatic layer 11, a transparent resin film 12, and an adhesive layer 13 in sequence.
[0024] Figure 2The surface protective film 15 shown is in the position of... Figure 1 The surface protective film 10 is peeled off from the release film 14 and the adhesive layer 13 is able to adhere to the object 21. Figure 3 The optical component 20 shown is manufactured by attaching a surface protective film 15, in which the isolation film 14 has been peeled off, to the substrate 21.
[0025] In the surface protective films 10 and 15 of this embodiment, the thickness of the adhesive layer 13 is preferably 12 μm to 25 μm, more preferably 15 μm to 25 μm, and even more preferably 15 μm to 20 μm. If the thickness of the adhesive layer 13 is within the above range, sufficient adhesive force can be exerted on the polarizing plate, which is the adherend 21, and residual adhesive can be suppressed during peeling.
[0026] For the surface protective films 10 and 15 in this embodiment, the storage modulus G' of the surface protective film 15 in the state where the isolation film 14 has been peeled off from the surface protective film 10 is preferably 1.8 × 10⁻⁶. 5 Pa or less, more preferably 1.5 × 10 Pa. 5 Pa below, more preferably 1.3 × 10 Pa 5 Pa or less. If the energy storage modulus is within the above range, it can be well bonded to the polarizing plate 21 as the adherend, and has a low elastic modulus, so it can follow well even for polarizing plates with uneven surfaces with a surface roughness of 200 nm or more.
[0027] Furthermore, for the surface protective films 10 and 15 of this embodiment, after the surface protective film 15, in which the release film 14 has been peeled off from the surface protective film 10, is adhered to the polarizing plate, which serves as the substrate 21, the peeling force when peeled from the polarizing plate at a peeling angle of 180° and a peeling speed of 30 m / min is preferably 1.7 N / 25 mm or less, more preferably 1.5 N / 25 mm or less. If the peeling force is within the above range, the surface protective films 10 and 15 of this embodiment can exhibit high easy peeling properties.
[0028] Furthermore, regarding the surface protective films 10 and 15 of this embodiment, when the surface protective film 15, in which the release film 14 has been peeled off from the surface protective film 10, is subjected to a pressure of 2 kgf / cm 2 (19.6133 N / cm) 2 The proportion of the area of the bubble before pressurization within the measured field of view, which is attached to the polarizing plate as the substrate 21, is set as A. A pressure of 5 kgf / cm² is applied. 2 (49.03325 N / cm) 2When B is defined as the proportion of the bubble area after localized pressure application for 10 seconds within the measured field of view, the bubble area change rate A-B is preferably 3.0% or less, more preferably less than 3.0%, and even more preferably 2.9% or less. Therefore, when bubbles are trapped between the polarizing plate with a large surface unevenness and the adhesive layer, even with localized pressure application, discoloration compared to other areas (areas without pressure) can be suppressed. Regarding discoloration, for example, there may be cases where optical interference occurs around the bubbles, and iridescence is observed as the direction changes with time, line of sight, etc.
[0029] As a polarizing plate with a relatively large surface roughness, an example is a polarizing plate with a surface roughness Ra of 200 nm or more, as described above. As a surface treatment for polarizing plates, examples include anti-glare (AG) treatment or anti-glare coating. Low-reflection (AGLR) treatment. Surfaces that have undergone AG or AGLR treatment can be further treated with hard coating (HC). Polarizing plates can also be treated with only AG or AGLR treatment without HC treatment. The surface substrate for polarizing plates is not particularly limited and can include triacetate cellulose (TAC) film, acrylic film, cyclic polyolefin film, polyester film, etc.
[0030] The antistatic layer 11 preferably contains at least an antistatic agent, and may further contain polyether-modified silicone additives. The inherent surface resistivity of the antistatic layer 11 is preferably 1.0 × 10⁻⁶. 10 Below Ω / □. If the inherent surface resistivity is greater than the above range, there is a risk that the antistatic effect cannot be obtained in the optical component 20 formed by attaching the surface protective film 15 to the polarizing plate, so it is not preferred.
[0031] Examples of antistatic agents are not particularly limited and include alkali metal salts, anionic surfactants, cationic surfactants, ionic compounds with organic cations and anions or inorganic anions, conductive polymers, and conductive substances such as carbon. Antistatic agents preferably contain conductive polymers, but may also consist solely of conductive polymers.
[0032] As conductive polymers, without particular limitation, examples include known compounds such as polythiophene-based, polyacetylene-based, polypyrrole-based, polyaniline-based, and poly(p-phenylene)-based compounds. Conductive polymers can have substituents such as alkyl, phenyl, and ether groups, and can also form salts with dopants such as sulfonic acids.
[0033] Examples of polyether-modified silicone additives include silicone compounds modified with polyether chains. Examples of epoxy alkyl units constituting the polyether chain include ethylene oxide units and propylene oxide units. The polyether chain can contain one or more epoxy alkyl units. Examples of terminal groups on the opposite side of the polyether chain and the polysiloxane chain include hydroxyl and alkoxy groups. By selecting the molecular weight of the polyether chain used in the side chain of the polyether-modified silicone compound and its mass ratio to the polysiloxane chain, desired hydrophobic and other physical properties can be adjusted.
[0034] The transparent resin film 12 is not particularly limited, but preferably is a polyester film such as polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, or polybutylene terephthalate. Besides polyester films, films composed of other resins can also be used as long as they possess the required strength and optical adaptability. If the transparent resin film 12 is used as the substrate film for the adhesive layer 13, the appearance inspection of the optical component 20 can be performed while the surface protective film 15 is attached.
[0035] The transparent resin film 12 can be any of an unstretched film, a uniaxially stretched film, or a biaxially stretched film. Furthermore, the stretching ratio of the stretched film and the orientation angle of the axial direction formed during crystallization can be controlled to specific values. The thickness of the transparent resin film 12 is not particularly limited; for example, 12 μm to 100 μm is preferred, and 20 μm to 75 μm is easier to handle and therefore more preferred. If necessary, surface modification based on corona discharge, coating with an anchoring agent, or other adhesion-enhancing treatments can be applied to the surface of the substrate film.
[0036] As the adhesive layer 13 on one side of the transparent resin film 12, for example, acrylic adhesives, polyurethane adhesives, silicone adhesives, etc., can be used, and it is preferable to be an adhesive layer that is as transparent as the transparent resin film 12. As an acrylic adhesive layer composed of an acrylic adhesive, an adhesive layer formed by crosslinking an adhesive composition containing an acrylic polymer and a crosslinking agent can be cited as an example.
[0037] As an acrylic polymer, examples include copolymers formed by copolymerizing a main monomer with a comonomer and / or a functional monomer. The main monomer may be one or more selected from n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, isononyl acrylate, etc. The comonomer may be one or more selected from acrylonitrile, vinyl acetate, methyl methacrylate, ethyl acrylate, (meth)acrylates containing polyoxyalkylene groups. The polyoxyalkylene groups may include polyoxyethylene, polyoxypropylene, etc. (Meth)acrylates refer to acrylates and / or methacrylates. The functional monomer may be one or more selected from acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxybutyl acrylate, glycidyl methacrylate, N-hydroxymethylmethacrylamide, etc.
[0038] For the crosslinking agent, one or more selected from isocyanate compounds, epoxy compounds, melamine compounds, metal chelate compounds, etc., can be used as crosslinking agents for crosslinking acrylic polymers. The crosslinking agent can be a curing agent capable of reacting with the functional groups of functional monomers. The adhesive layer 13 may optionally contain a tackifier. Examples of tackifiers include rosin-based, coumarone-indene-based, terpene-based, petroleum-based, and phenol-based agents. The adhesive layer 13 may also contain any other additives.
[0039] The adhesive layer 13 preferably comprises an antistatic agent and / or polyether-modified silicone. The antistatic agent and the antistatic agent contained in the antistatic layer 11 can be the same type of antistatic agent or different types of antistatic agent. The polyether-modified silicone and the polyether-modified silicone contained in the antistatic layer 11 can be the same type of polyether-modified silicone or different types of polyether-modified silicone.
[0040] The release film 14 is not particularly limited, and examples include release films formed by creating a release agent layer on the surface of a transparent resin film using a release agent. Silicone-based release agents are suitable as the release agent. Silicone-based release agents are not particularly limited, and examples include known silicone-based release agents such as addition reaction type, condensation reaction type, cationic polymerization type, and free radical polymerization type.
[0041] The resin film used in the substrate film of the release agent layer can be the same polyester film as the transparent resin film 12. In addition to polyester films, films composed of other resins can also be used as long as they have the required strength and optical adaptability. If the release film 14 is transparent, the surface protective films 10 and 15 can be visually inspected while the release film 14 is adhered to the adhesive layer 13.
[0042] The method for forming the antistatic layer 11 or adhesive layer 13 on the surface of the transparent resin film 12 is not particularly limited, as long as a known method is used. Specifically, known coating methods such as reverse roller coating, comma coating, gravure coating, slot coating, Mayer rod coating, and air knife coating can be cited.
[0043] Surface protective films 10 and 15 can be used on optical components 20 bonded to substrate 21 after the release liner 14 has been peeled off. Examples of substrates 21 for optical components 20 include polarizing plates, retardation plates, lens films, anti-reflective films, hard coatings, and transparent conductive films for touch panels. Substrate 21 can be two or more optical films that combine the functions of the aforementioned optical films.
[0044] The optical component 20 can be mounted on an electronic device. Examples of electronic devices include liquid crystal display devices such as liquid crystal display panels and optical devices for various instruments.
[0045] Example The present invention will now be specifically described using examples.
[0046] (Preparation of the antistatic layer) The antistatic agent dispersion, the resin composition of the adhesive, the methylated melamine crosslinking agent (manufactured by CARBIDE Industries, Ltd., Japan, NIKALAC (registered trademark) MW-30HM), and the polyether-modified silicone additive (manufactured by Shin-Etsu Chemical Co., Ltd., KF-352) were adjusted according to a solid component mass ratio of 30 / 100 / 30 / 3. The mixture was diluted 10 times with a water / ethanol (water / ethanol mass ratio 50 / 50) mixture to obtain an antistatic coating. The obtained antistatic coating was applied to the surface of a 38μm thick polyethylene terephthalate film (PET film, substrate film) to achieve a dried antistatic layer thickness of 0.2μm. The coating was then dried in a hot air circulating oven at 120°C for 1 minute. This formed an antistatic layer on the PET film.
[0047] The types of resin components used in the production of antistatic agents and adhesives for antistatic layers are shown below.
[0048] As an antistatic agent, a conductive polymer (manufactured by AGFA Corporation, Orgacon (registered trademark) ICP 1021) or nano carbon (manufactured by Nagase ChemteX Co., Ltd., Denatron (registered trademark) CD-100) is used.
[0049] The resin component used as the adhesive is polyvinyl alcohol (PVA) resin (Kuraray Poval (registered trademark) 3-88) or polyester resin (Plascoat (registered trademark) RZ-570) manufactured by Koyo Chemical Industry Co., Ltd.
[0050] (Preparation of the adhesive layer) An acrylic adhesive was prepared by means of a copolymer comprising 80 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, and 3 parts by weight of 2-hydroxyethyl acrylate. A specified amount of isocyanate-based curing agent (manufactured by Asahi Kasei Corporation, Durnate (registered trademark) MFA-75B) as a crosslinking agent was added to 100 parts by weight of a 40% ethyl acetate solution of this acrylic adhesive, and the mixture was mixed to obtain an adhesive composition. The adhesive composition was applied to the surface of a PET film without the antistatic layer, using a coating machine, to achieve a specified thickness of the dried adhesive layer. The coating was then dried in a hot air circulating oven at 120°C for 3 minutes to form an adhesive layer.
[0051] The ratio (parts by weight) of the crosslinking agent to 100 parts by weight of the adhesive and the thickness (μm) of the dried adhesive layer are shown in Table 1. Additionally, in Examples 5 and 6, 1.0 part by weight of an antistatic agent (lithium bis(fluorosulfonyl)imide) was added relative to 100 parts by weight of the adhesive. Furthermore, in Example 6, 1.0 part by weight of an additive (polyether-modified silicone) (manufactured by Shin-Etsu Chemical Industry Co., Ltd., KF-352A) was added relative to 100 parts by weight of the adhesive.
[0052] (Preparation of surface protective film) A release film (25 μm thick) treated with a silicone-based release agent (manufactured by Mitsubishi Chemical Corporation, DIAFOIL (registered trademark) MRF-25) was laminated onto the surface of the adhesive layer as a release liner to obtain a surface protective film with a release liner. The obtained surface protective film with a release liner was cured at 40°C for 3 days.
[0053] (Method for determining the storage modulus G' of the surface protective film) The protective film, with the release film (isolating film) removed, was clamped and mounted on the solid shear fixture, an optional accessory of the viscoelasticity measuring device (product name "Rheogel-E4000", manufactured by UBM Corporation). The value of G' was measured in shear mode at 23°C and 1Hz.
[0054] (Methods for measuring the inherent resistivity of a surface) The inherent surface resistivity (Ω / □) of the antistatic layer of the surface protective film was measured using a high-performance high resistivity meter (manufactured by Nitto Seiko Analytech Co., Ltd., Hiresta (registered trademark)-UP) under conditions of an applied voltage of 100V and a measurement time of 30 seconds.
[0055] In Table 1, exponential notation is used to record the values of the storage modulus G' and the intrinsic surface resistivity. Exponential notation means that when the number before E is set to m and the number after E is set to n, it represents m × 10⁻⁶. n .
[0056] (Method for determining peel strength) AG-based polarizing plates with different surface roughness were bonded to the surface of a glass plate using a laminating machine. A protective film, cut to a width of 25 mm, was then bonded to the surface of the polarizing plate. The polarizing plate with the protective film was stored for one day at a test environment of 23°C and 50% RH. The peel strength (N / 25 mm) of the protective film was measured using a high-speed peel tester (manufactured by TESUTA Sangyo Co., Ltd.) at a peel speed of 30 m / min.
[0057] (Method for confirming color change) A laminating machine was used to bond AG-based polarizing plates with different surface roughnesses, each measuring 100mm x 100mm, to the surface of a glass plate. The bonding agent on the polarizing plate surface was 12 kgf / cm². 2 The pressure is applied to a surface protective film with a size of 100mm × 100mm. Using the clamping rollers of the laminator, a pressure of 5 kgf / cm is applied to the center portion of the surface protective film from above. 2 After applying pressure for 10 seconds, it was confirmed that there was no color change compared to other parts. It should be noted that, by definition, 1 kgf equals 9.80665 N. In Table 2, no color change is recorded as OK, and color change is recorded as NG.
[0058] (Method for determining the area ratio of air bubbles) The unpressurized and pressurized areas were observed using a DSX1000 microscope (manufactured by Olympus Corporation). The percentage of bubble area (%) identified within a 1.9mm × 1.9mm field of view was measured at a magnification of 140x. The percentage of bubble area before pressurization is designated as A, and the percentage of bubble area after pressurization is designated as B. Table 2 shows the difference between the percentage of bubble area before pressurization (A) and the percentage of bubble area after pressurization (B), i.e., the bubble area change rate A-B, as a percentage (%).
[0059] [Table 1]
[0060] [Table 2]
[0061] As shown in Table 1, the proportion of crosslinking agent (isocyanate-based curing agent), the presence or absence of any additive (polyether-modified silicone), and the thickness of the adhesive layer were varied compared to the adhesive (acrylic polymer). In Table 2, the results were categorized according to the surface roughness of the polarizing plate (280nm, 340nm, 420nm).
[0062] In the surface protective films of Examples 1-6, peeling was easy under conditions where the peel force was less than 1.7 N / 25 mm, and the bubble area change rate A-B was less than 3.0%, thus suppressing discoloration of the optical components. In contrast, in the surface protective films of Comparative Examples 1, 3, 5, and 7, although the peel force was light, discoloration of the optical components could not be suppressed due to the influence of bubbles. It should be noted that these results also show that when the discoloration is NG, A-B becomes greater than 3.0%. Furthermore, in the surface protective films of Comparative Examples 2, 4, and 6, although discoloration of the optical components could be suppressed, the peel force was heavier.
Claims
1. A surface protective film for use on a polarizing plate with a surface roughness Ra of 200 nm or higher. The surface protective film comprises, in sequence, an antistatic layer, a transparent resin film, an adhesive layer, and a release film. The thickness of the adhesive layer is 12μm to 25μm. The storage modulus G' of the state in which the isolation film has been peeled off from the surface protective film is 1.8 × 10⁻⁶. 5 Below Pa, After being attached to the polarizing plate with the release film peeled off from the surface protective film, the peeling force when peeled off from the polarizing plate at a peeling angle of 180° and a peeling speed of 30m / min is less than 1.7N / 25mm. When the release film has been peeled off from the surface protective film and a pressure of 2 kgf / cm is applied... 2 Let A be the proportion of the bubble area before pressurization within the measured field of view, attached to the polarizing plate. A pressure of 5 kgf / cm² will be applied. 2 When the proportion of the bubble area after localized pressurization for 10 seconds within the measured field of view is set as B, the bubble area change rate A-B is less than 3.0%.
2. The surface protective film according to claim 1, wherein, The polarizing plate has been treated with anti-glare or anti-glare coating. Low-reflection treatment.
3. The surface protective film according to claim 1, wherein, The antistatic layer comprises a conductive polymer and a polyether-modified silicone additive. The surface resistivity of the antistatic layer is 1.0 × 10⁻⁶. 10 Below Ω / □.
4. The surface protective film according to claim 1, wherein, The adhesive layer is formed by crosslinking an adhesive composition containing an acrylic polymer and a crosslinking agent.
5. The surface protective film according to claim 4, wherein, The adhesive layer also contains an antistatic agent and / or polyether-modified silicone.
6. An optical component, wherein the surface protective film of any one of claims 1 to 5 is adhered to the polarizing plate in a state in which the isolation film has been peeled off.
7. An electronic device equipped with the optical component of claim 6.